A mildew-proof, flame-retardant and formaldehyde-removing masterbatch and preparation method thereof
By using components such as nanosilver particles and nanocomposites in plastic masterbatches, combined with modified aqueous epoxy resin emulsion and twin-screw extrusion granulation technology, the existing plastic masterbatches have been solved by poor anti-mold and flame retardant properties. The poor problem has achieved efficient anti-mold, flame retardant and formaldehyde removal effects, improving the stability and safety of the material.
Patent Information
- Application Number
- CN202411125035.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-16
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-08-16
AI Technical Summary
The existing plastic masterbatches are easy to decompose antibacterial substances in high salt and high humidity environments, have limited anti-mold effects, and have poor flame retardant properties, which can easily lead to fire spread. The decoration materials often contain chemical additives, resulting in excessive formaldehyde.
Use anti-mold, flame-retardant formaldehyde removal masterbatch composed of nanosilver particles, nanocomposite materials, modified aqueous epoxy resin emulsion, plastic masterbatch base material, isophthalamine, coupling agent and antioxidant. By modification The uniform mixing of aqueous epoxy resin emulsion and nanocomposite materials and twin screw extrusion granulation technology form a stable and efficient anti-mold, flame retardant and formaldehyde removal effect.
It achieves a stable anti-mold effect in a high salt and high humidity environment, improves flame retardant performance, slows down the spread of fire, significantly reduces the formaldehyde concentration, and improves the fire resistance time and quality of the material.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of plastic masterbatches and relates to a mildew-proof, flame-retardant and formaldehyde-removing masterbatch and a preparation method thereof. Background Art
[0002] Molds are two main types of microorganisms, with a wide variety, wide distribution, and strong vitality. When the environmental conditions are relative humidity greater than 65%, temperature 20~30℃, and pH value 3.0~6.0, they will quickly absorb nutrients on the surface of the material and grow, causing the material to mold and damage. At present, antimicrobial agents are often added to masterbatches to obtain plastic products with antimicrobial effects. Antimicrobial agents mainly include organic antimicrobial agents and inorganic antimicrobial agents. Organic antimicrobial agents include quaternary ammonium salts, imidazoles, pyridines, organic metals, etc. Inorganic antimicrobial agents are mainly inorganic substances such as silver, copper, and zinc, which mainly use their oxidative activity and free ions to kill fungi.
[0003] However, due to the high salt and high humidity environment, antibacterial substances are easily decomposed and released quickly. Therefore, the anti-mildew and antibacterial effects of most antibacterial masterbatches on plastic products are limited, so there is room for improvement.
[0004] At present, most decoration materials sold on the market contain chemical additives and chemical compounds, and it is difficult for ordinary people to effectively distinguish between various types of decoration materials, which often causes formaldehyde in newly decorated indoor spaces to exceed the standard. In addition, its flame retardant performance is relatively poor, and the generation of molten droplets can easily spread the fire, increase the probability of fire, the level of accidents and the difficulty of disaster relief, which also affects its quality to a certain extent.
[0005] Based on this, the present invention provides a masterbatch that can simultaneously prevent mildew, flame retardant and remove formaldehyde. Summary of the invention
[0006] The purpose of the present invention is to provide a mildew-proof, flame-retardant and formaldehyde-removing masterbatch and a preparation method thereof. The plastic masterbatch prepared by the present invention has mildew-proof, flame-retardant and formaldehyde-removing effects, and is stable and efficient in use.
[0007] The purpose of the present invention can be achieved by the following technical solutions:
[0008] A mildew-proof, flame-retardant and formaldehyde-removing masterbatch, which is composed of the following components in parts by weight: 10-20 parts of nano-silver particles, 3-6 parts of nano-composite materials, 100-200 parts of modified waterborne epoxy resin emulsion, 60-75 parts of plastic masterbatch base material, 3-6 parts of meta-xylylenediamine, 2-5 parts of coupling agents and 1-3 parts of antioxidants;
[0009] The modified waterborne epoxy resin emulsion is prepared by the following steps:
[0010] S11. At 35-40°C, stir 2-4 parts of emulsifier and 10-20 parts of deionized water to make them completely dissolved, thereby obtaining an emulsifier solution;
[0011] S12, take 5-10 parts of carboxyethyl cellulose, add 10-20 parts of deionized water, stir at a temperature of 100-110°C until completely dissolved to obtain a cellulose solution, and fully stir the fiber solution and the emulsifier solution in a mass ratio of 1:1;
[0012] S13, heating to 120-125°C, adding 40-60 parts of waterborne epoxy resin, 5-10 parts of glycidyl methacrylate, and 1-2 parts of sodium dodecylbenzene sulfonate, stirring evenly, adding 1-3 parts of initiator benzoyl peroxide, stirring at a speed of 600-800 r / min, and keeping warm for 4-5 hours, then cooling to 45-55°C, adding N,N-dimethylethanolamine to adjust the pH of the solution to 7-8, keeping warm for 0.5-1 hour at 40-45°C, filtering, and then adding 10-20 parts of waterborne acrylate emulsion and mixing well to obtain a modified waterborne epoxy resin emulsion;
[0013] The nanocomposite material is prepared by the following steps:
[0014] S21, placing the zeolite in a nitric acid solution with a mass fraction of 13-20% for 2-3 hours, taking it out and drying it to obtain the acid-treated zeolite;
[0015] S22, add 1-3 parts of acid-treated zeolite to 10-50 parts of 3-7 mol / L magnesium chloride aqueous solution, adjust the pH to 8-9, react for 0.5-1 hour, calcine at 320-380° C. for 5-8 hours under nitrogen protection, and deposit magnesium oxide on the surface of the zeolite by in-situ deposition method after cooling to room temperature;
[0016] S23, fully dissolving 3-aminopropyltriethoxysilane with anhydrous ethanol to prepare a solution with a mass fraction of 40-50%, adding 15-25 parts of the solid obtained in step S22 to 20-35 parts of the solution, stirring at a speed of 500 r / min for 5-10 min, filtering after standing for 2-3 hours, washing with deionized water, and drying the filter residue in a vacuum drying oven at a temperature of 110-120° C. for 3-5 hours to obtain amination solid particles;
[0017] S24, at 60°C, 40 parts of 0.32-0.35 mol / L nickel acetate tetrahydrate in anhydrous ethanol and 10 parts of 0.2 mol / L phytic acid ethanol solution were mixed, and then 20-25 parts of nano titanium dioxide were added, and the temperature was raised to 80-90°C and stirred for reaction for 2 hours, and modified nano titanium dioxide was prepared by centrifugation, ethanol washing, drying, and grinding;
[0018] S25, grinding 15 to 20 parts of the aminated solid particles and 15 parts of nano-titanium dioxide in a ball mill at a rotation speed of 400 r / min for 4 to 6 hours to obtain the nano-composite material.
[0019] As a preferred technical solution of the present invention, the coupling agent is one of vinyltrimethoxysilane, vinyltriethoxysilane and vinyltri(2-methoxyethoxy)silane.
[0020] As a preferred technical solution of the present invention, the antioxidant is antioxidant 1010 or antioxidant 168.
[0021] As a preferred technical solution of the present invention, in step S11, the emulsifier is one of OP-10, Tween-80 and Span-80.
[0022] A method for preparing a mildew-proof, flame-retardant and formaldehyde-removing masterbatch comprises the following steps:
[0023] S51, adding nano silver particles and nano composite materials to the modified waterborne epoxy resin emulsion according to the proportion, stirring at a speed of 600-700 r / min for 2-3 hours to obtain a suspension;
[0024] S52, maintaining the stirring speed, adding the plastic masterbatch base material, m-xylylenediamine, coupling agent and antioxidant into the suspension, uniformly mixing for 2-3 hours and then drying to obtain a mixture;
[0025] S53. The mixed material is passed through a twin-screw extruder granulator, and then melt blended, extruded, and pelletized to prepare the mildew-proof, flame-retardant, and formaldehyde-removing masterbatch. The temperature settings of the twin-screw extruder granulator are as follows: 160-210°C for the feeding section, 170-240°C for the compression section, 175-265°C for the homogenization section, 5-20r / min for the feeding speed, 200-350r / min for the screw speed, and 8-12m / min for the pelletizing speed.
[0026] As a preferred technical solution of the present invention, in step S51, the concentration of the suspension is 0.3-0.6 mg / mL.
[0027] As a preferred technical solution of the present invention, in step S51, the particle size of the nano silver particles is 40-60 μm.
[0028] As a preferred technical solution of the present invention, in step S52, the plastic masterbatch substrate is one of polypropylene, polyethylene terephthalate, acrylonitrile-butadiene-styrene plastic and thermoplastic polyurethane elastomer.
[0029] As a preferred technical solution of the present invention, in step S52, the drying method is to place the mixture in a drying tunnel at 150-190° C. and dry it for 5-7 minutes.
[0030] Beneficial effects of the present invention:
[0031] When preparing the modified waterborne epoxy resin in the present invention, the carboxyethyl cellulose and the emulsifier are first mixed uniformly, which can further enhance the ability of the emulsifier to reduce the interfacial tension and make the emulsion more stable. In addition, the carboxyethyl cellulose contains hydrophilic groups, such as carboxyl and hydroxyl groups, which can form hydrogen bonds with water molecules, thereby improving the water resistance of the emulsion and providing a more uniform reaction environment for the waterborne epoxy resin and the monomer methacrylate glycidyl ether to react under the action of an initiator, so that the monomer molecules are more likely to approach the waterborne epoxy resin and undergo a polymerization reaction. The epoxy resin contains ether bonds on its molecular chain, and the α-H on the adjacent carbon atoms and the hydrogen atoms on the tertiary carbon atoms are relatively active, and react with the methacrylate glycidyl ether under the action of an initiator. The grafting polymerization reaction of the hydroxyl groups in the ether can improve the hydrophilicity of the epoxy resin emulsion, thereby improving the compatibility between the water-based epoxy resin and the nano-silver particles and the nano-composite material; and because the hydroxyl groups in the carboxyethyl cellulose can form hydrogen bonds with the polar groups of the epoxy group or the hydroxyl groups in the water-based epoxy resin, it helps to form a stable interaction with the epoxy resin particles to prevent the particles from agglomerating, thereby obtaining a more uniform and delicate dispersion system. After the polymerization is completed, the weather resistance of the emulsion can be improved after blending with the water-based acrylic ester emulsion. At the same time, the long-chain molecular structure of the carboxyethyl cellulose will be entangled with the water-based epoxy resin and acrylic ester to form a physical network structure, thereby enhancing the interaction between molecules.
[0032] The modified water-based epoxy resin emulsion is first mixed with nano-silver particles and nano-composite materials to promote the uniform distribution of the nano-particles in the modified water-based epoxy resin emulsion and reduce the occurrence of agglomeration. After being evenly mixed, it is dried. During the drying process, the water in the modified water-based epoxy resin evaporates, and the modified epoxy resin particles contact and condense with each other, thereby helping the nano-materials to form a large number of interface areas between the epoxy resins and maintain uniform stability.
[0033] Treating zeolite with nitric acid can remove impurities such as SiO2, Fe2O3 and organic matter inside the zeolite, and the H with a small radius + Will displace Na with a larger radius + , Ca 2+Cations, which not only helps to remove these cations, but also can further widen the effective space of the pores, and improve the adsorption performance of zeolite for formaldehyde; in the present invention, magnesium oxide is deposited on the surface of zeolite by an in-situ adsorption method, and then the zeolite with magnesium oxide deposited on the surface is subjected to an amination treatment by 3-aminopropyltriethoxysilane, so as to further optimize the surface properties and pore size of the zeolite and increase the adsorption capacity for formaldehyde; formaldehyde molecules are adsorbed and fixed by the rich microporous structure on the surface of the zeolite, and the molecular sieve effect is used to prevent formaldehyde from precipitating from the pores. At the same time, the large amount of negative charges on the surface of the acid-treated zeolite will generate electrostatic effects with formaldehyde, making formaldehyde more easily adsorbed on the surface. When formaldehyde is fixed, the magnesium oxide deposited on the zeolite removes formaldehyde by further adsorption and catalytic decomposition, and the removal rate of formaldehyde is improved by the joint action of the two. When the zeolite and magnesium oxide jointly adsorb and fix formaldehyde, the amino groups on the surface will chemically react with formaldehyde to improve the removal rate of formaldehyde;
[0034] Nickel phytate is prepared by reacting nickel acetate tetrahydrate with phytic acid. The nickel ions in nickel phytate react with the hydroxyl groups (-OH) on the surface of nano-titanium dioxide to form a stable chemical bond. The nickel ions are stably bound to the surface of nano-titanium dioxide by the complexing ability of nickel phytate to form a uniform covering layer. Nickel phytate can be used as a flame retardant to form a highly expanded and compact carbon layer with a cross-linking reaction with the matrix material, which effectively isolates the transfer of heat and oxygen, thereby slowing down or preventing further combustion of the material. Nano-titanium dioxide modified with nickel phytate has a further improved anti-mold effect due to the combination of nickel ions on the surface of nickel phytate with the active groups on the surface of titanium dioxide. At the same time, nickel phytate changes the charge distribution on the surface of nano-titanium dioxide, which can promote the separation of photogenerated electrons and holes in nano-titanium dioxide, promote photocatalytic efficiency, and thus improve the removal rate of formaldehyde.
[0035] Due to its high specific surface area and special crystal structure, magnesium oxide can effectively absorb and disperse heat at high temperatures, thereby significantly improving the flame retardant properties of the material. Nano titanium dioxide can also improve the flame retardant properties of the material by absorbing heat and cooling, and capturing free radicals. Zeolite can maintain good stability at high temperatures. At the same time, the porous structure of zeolite can absorb and store a large amount of heat, slowing down the temperature increase of the material. When nano magnesium oxide, nano titanium dioxide and zeolite are compounded, they will work synergistically with each other. Nano magnesium oxide and amino nano titanium dioxide can form a protective layer on the surface of the material, while the porous structure of zeolite can absorb and store a large amount of heat. After the three are compounded, a more dense and stable protective layer can be formed, which improves the fire resistance time and flame retardant properties of the material and jointly improves the flame retardant properties of the composite material. And through the compounding of the three, the photocatalytic activity of nano titanium dioxide can be improved, the separation of photogenerated electron-hole pairs can be promoted, thereby extending the life of photogenerated carriers and improving photocatalytic efficiency.
[0036] Nanosilver particles mainly interact with mold microorganisms, effectively inhibiting the growth and reproduction of mold microorganisms by destroying cell membranes, inhibiting enzyme activity, interfering with biological metabolism, and releasing silver ions, thereby achieving excellent anti-mold effects. Nanosilver can also quickly decompose formaldehyde through photocatalysis, improving the efficiency of formaldehyde removal, and the stability of nanosilver particles enables it to maintain catalytic activity for a long time, achieving a long-lasting formaldehyde removal effect. DETAILED DESCRIPTION
[0037] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0038] In the following examples and comparative examples:
[0039] Water-based acrylic emulsion: purchased from Shanghai Baolijia Chemical Co., Ltd., model BLJ-719;
[0040] The particle size of nanosilver particles is 40~60μm.
[0041] Nanosilver particles: from Shanghai Yinzhidao Nanotechnology Co., Ltd.;
[0042] Nano-titanium dioxide: 100 nm, purchased from Qinghe County Ruijiang Metal Materials Co., Ltd.;
[0043] Polypropylene PP: purchased from Jinzhicheng Plastic Technology Co., Ltd.;
[0044] OP-10: purchased from Shandong Zhengxing New Materials Co., Ltd., brand: Zhengxing;
[0045] Water-based epoxy resin: purchased from Wuhan Penglei Biotechnology Co., Ltd.;
[0046] Carboxyethyl cellulose: purchased from Wuhan Xingzhongcheng Technology Co., Ltd.;
[0047] Methacrylate glycidyl ether: purchased from Wuhan Rongcan Biotechnology Co., Ltd.;
[0048] Sodium dodecylbenzene sulfonate: purchased from Jinan Shanhai Chemical Technology Co., Ltd., product number: LAS01;
[0049] Benzoyl peroxide: purchased from Shanghai Myrel Biochemical Technology Co., Ltd., product number: M29988;
[0050] 3-Aminopropyltriethoxysilane: purchased from Hubei Yongkuo Technology Co., Ltd.;
[0051] Magnesium chloride: purchased from Hubei Xinmingtai Chemical Co., Ltd.;
[0052] Vinyltrimethoxysilane: purchased from Hubei Zhenbo Chemical Co., Ltd., product number: ZB190;
[0053] Vinyl triethoxysilane: purchased from Tesco Chemical (Hubei) Co., Ltd.;
[0054] Antioxidant 168: purchased from Wuhan Kanos Technology Co., Ltd.;
[0055] Antioxidant 1010: purchased from Wuhan Rongcan Biotechnology Co., Ltd.;
[0056] Polyethylene terephthalate PET: purchased from Hubei Qifei Pharmaceutical Chemical Co., Ltd.;
[0057] Tween-80: purchased from Shandong Tiandao Bioengineering Co., Ltd.;
[0058] Nickel acetate tetrahydrate: purchased from Hubei Tosoh Chemical Technology Co., Ltd.;
[0059] Phytic acid: purchased from Beijing Bailingwei Technology Co., Ltd., product number: 388440.
[0060] Example 1
[0061] Preparation of modified waterborne epoxy resin emulsion:
[0062] S11. At 35°C, stir 2 parts of OP-10 and 10 parts of deionized water to make them completely dissolved to obtain an emulsifier solution;
[0063] S12, take 5 parts of carboxyethyl cellulose, add 10 parts of deionized water, stir at a temperature of 100°C until completely dissolved to obtain a cellulose solution, and fully stir the fiber solution and the emulsifier solution in a mass ratio of 1:1;
[0064] S13, heat to 120 ° C, add 40 parts of water-based epoxy resin, 5 parts of glycidyl methacrylate, 1 part of sodium dodecylbenzene sulfonate, stir evenly, add 1 part of initiator benzoyl peroxide, stir at a speed of 600r / min, keep warm for 4 hours, then cool to 45 ° C, add N, N-dimethylethanolamine to adjust the pH of the solution to 7, keep warm at 40 ° C for 0.5 h, filter, add 10 parts of water-based acrylate emulsion and mix well to obtain modified water-based epoxy resin emulsion.
[0065] Preparation of nanocomposites:
[0066] S21, placing the zeolite in a nitric acid solution with a mass fraction of 13% for 3 hours, taking it out and drying it to obtain an acid-treated zeolite;
[0067] S22, adding 1 part of acid-treated zeolite to 10 parts of 3 mol / L magnesium chloride aqueous solution, adjusting the pH to 8 and reacting for 0.5 h, calcining at 320° C. for 8 h under nitrogen protection, and then cooling to room temperature to deposit magnesium oxide on the surface of the zeolite by in-situ deposition method;
[0068] S23, fully dissolving 3-aminopropyltriethoxysilane with anhydrous ethanol to prepare a solution with a mass fraction of 40%, adding 15 parts of the solid obtained in step S22 to 20 parts of the solution, stirring at a speed of 500 r / min for 5 minutes, filtering after standing for 2 hours, washing with deionized water, and drying the filter residue in a vacuum drying oven at a temperature of 110° C. for 3 hours to obtain amination solid particles;
[0069] S24, at 60°C, 40 parts of 0.32 mol / L nickel acetate tetrahydrate in anhydrous ethanol and 10 parts of 0.2 mol / L phytic acid ethanol solution were mixed, and then 20 parts of nano titanium dioxide were added, and the temperature was raised to 80°C and stirred for reaction for 2 hours, and modified nano titanium dioxide was prepared by centrifugation, ethanol washing, drying, and grinding;
[0070] S25, grinding 15 parts of the aminated solid particles and 15 parts of nano-titanium dioxide in a ball mill at a rotation speed of 400 r / min for 4 hours to obtain the nano-composite material.
[0071] Preparation of mildew-proof, flame-retardant and formaldehyde-removing masterbatch:
[0072] S51, adding 10 parts of nanosilver particles and 3 parts of nanocomposite materials to 100 parts of modified waterborne epoxy resin emulsion by mass, stirring at a speed of 600 r / min for 2 h to obtain a suspension with a concentration of 0.3 mg / mL;
[0073] S52, maintaining the stirring speed, adding 60 parts of PP, 3 parts of m-phenylenediamine, 2 parts of vinyltrimethoxysilane and 1 part of antioxidant 1010 to the suspension, uniformly mixing for 2 hours, and drying in a drying oven at 150° C. for 5 minutes to obtain a mixture;
[0074] S53. The mixed material is passed through a twin-screw extruder granulator, and then melt blended, extruded, and pelletized to obtain the mildew-proof, flame-retardant, and formaldehyde-removing masterbatch. The temperature settings of the twin-screw extruder granulator are as follows: 160°C for the feeding section, 170°C for the compression section, and 175°C for the homogenizing section. The feed speed is 5r / min, the screw speed is 200r / min, and the pelletizing speed is 8m / min.
[0075] Example 2
[0076] Preparation of modified waterborne epoxy resin emulsion:
[0077] S11. At 38°C, 3 parts of Tween-80 and 15 parts of deionized water were stirred thoroughly to completely dissolve to obtain an emulsifier solution;
[0078] S12, take 8 parts of carboxyethyl cellulose, add 18 parts of deionized water, stir at a temperature of 105°C until completely dissolved to obtain a cellulose solution, and fully stir the fiber solution and the emulsifier solution in a mass ratio of 1:1;
[0079] S13, heat to 122 ° C, add 50 parts of water-based epoxy resin, 8 parts of glycidyl methacrylate, 1 part of sodium dodecylbenzene sulfonate, stir evenly, add 2 parts of initiator benzoyl peroxide, stir at a speed of 700 r / min, keep warm for 4.5 hours, then cool to 50 ° C, add N, N-dimethylethanolamine to adjust the pH of the solution to 8, keep warm at 43 ° C for 0.8 h, filter, add 15 parts of water-based acrylate emulsion, mix well and evenly to obtain modified water-based epoxy resin emulsion.
[0080] Preparation of nanocomposites:
[0081] S21, placing the zeolite in a 16% by mass nitric acid solution for 2.5 hours, taking it out and drying it to obtain an acid-treated zeolite;
[0082] S22, adding 2 parts of acid-treated zeolite to 30 parts of 5 mol / L magnesium chloride aqueous solution, adjusting the pH to 8 and reacting for 0.8 h, calcining at 360° C. for 7 h under nitrogen protection, and then cooling to room temperature to deposit magnesium oxide on the surface of the zeolite by in-situ deposition method;
[0083] S23, fully dissolving 3-aminopropyltriethoxysilane with anhydrous ethanol to prepare a solution with a mass fraction of 45%, adding 20 parts of the solid obtained in step S22 to 28 parts of the solution, stirring at a speed of 500 r / min for 7 minutes, filtering after standing for 2.5 hours, washing with deionized water, and drying the filter residue in a vacuum drying oven at a temperature of 115° C. for 4 hours to obtain amination solid particles;
[0084] S24, at 60°C, 40 parts of 0.33 mol / L nickel acetate tetrahydrate in anhydrous ethanol and 10 parts of 0.2 mol / L phytic acid ethanol solution were mixed, and then 23 parts of nano titanium dioxide were added, and the mixture was heated to 85°C and stirred for 2 hours, and then centrifuged, washed with ethanol, dried, and ground to obtain modified nano titanium dioxide;
[0085] S25, grinding 18 parts of the amino solid particles and 15 parts of nano titanium dioxide in a ball mill at a rotation speed of 400 r / min for 5 hours to obtain the nanocomposite material.
[0086] Preparation of mildew-proof, flame-retardant and formaldehyde-removing masterbatch:
[0087] S51, adding 15 parts of nanosilver particles and 5 parts of nanocomposite materials to 150 parts of modified waterborne epoxy resin emulsion by mass, stirring the mixture at a speed of 650 r / min for 2.5 h to obtain a suspension with a concentration of 0.5 mg / mL;
[0088] S52, maintaining the stirring speed, adding 66 parts of PET, 4 parts of m-xylylenediamine, 4 parts of vinyltriethoxysilane and 2 parts of antioxidant 168 to the suspension, uniformly mixing for 2.5 hours, and drying in a drying oven at 170° C. for 6 minutes to obtain a mixture;
[0089] S53. The mixed material is passed through a twin-screw extruder granulator, and then melt blended, extruded, and pelletized to obtain the mildew-proof, flame-retardant, and formaldehyde-removing masterbatch. The temperature settings of the twin-screw extruder granulator are as follows: 180°C for the feeding section, 190°C for the compression section, and 210°C for the homogenizing section. The feeding speed is 14r / min, the screw speed is 290r / min, and the pelletizing speed is 10m / min.
[0090] Example 3
[0091] Preparation of modified waterborne epoxy resin emulsion:
[0092] S11. At 40°C, stir 4 parts of OP-10 and 20 parts of deionized water to make them completely dissolved to obtain an emulsifier solution;
[0093] S12, take 10 parts of carboxyethyl cellulose, add 20 parts of deionized water, stir at a temperature of 110°C until completely dissolved to obtain a cellulose solution, and fully stir the fiber solution and the emulsifier solution in a mass ratio of 1:1;
[0094] S13, heat to 125 ° C, add 60 parts of water-based epoxy resin, 10 parts of glycidyl methacrylate, 2 parts of sodium dodecylbenzene sulfonate, stir evenly, add 3 parts of initiator benzoyl peroxide, stir at a speed of 800 r / min, keep warm and react for 5 hours, then cool to 55 ° C, add N, N-dimethylethanolamine to adjust the pH of the solution to 8, keep warm and react at 45 ° C for 1 hour, filter, add 20 parts of water-based acrylate emulsion and mix well to obtain modified water-based epoxy resin emulsion.
[0095] Preparation of nanocomposites:
[0096] S21, placing the zeolite in a 20% by mass nitric acid solution for treatment for 2 hours, taking it out and drying it to obtain an acid-treated zeolite;
[0097] S22, adding 3 parts of acid-treated zeolite to 50 parts of 7 mol / L magnesium chloride aqueous solution, adjusting the pH to 9 and reacting for 1 hour, calcining at 380° C. for 5 hours under nitrogen protection, and then cooling to room temperature to deposit magnesium oxide on the surface of the zeolite by in-situ deposition method;
[0098] S23, fully dissolving 3-aminopropyltriethoxysilane with anhydrous ethanol to prepare a solution with a mass fraction of 50%, adding 25 parts of the solid obtained in step S22 to 35 parts of the solution, stirring at a speed of 500 r / min for 10 minutes, filtering after standing for 3 hours, washing with deionized water, and drying the filter residue in a vacuum drying oven at a temperature of 120° C. for 5 hours to obtain amination solid particles;
[0099] S24, at 60°C, 40 parts of 0.35 mol / L nickel acetate tetrahydrate in anhydrous ethanol and 10 parts of 0.2 mol / L phytic acid ethanol solution were mixed, and then 25 parts of nano titanium dioxide were added, and the mixture was heated to 90°C and stirred for reaction for 2 hours, and then centrifuged, washed with ethanol, dried, and ground to obtain modified nano titanium dioxide;
[0100] S25, grinding 20 parts of the aminated solid particles and 15 parts of nano-titanium dioxide in a ball mill at a rotation speed of 400 r / min for 6 hours to obtain the nano-composite material.
[0101] Preparation of mildew-proof, flame-retardant and formaldehyde-removing masterbatch:
[0102] S51, adding 20 parts of nanosilver particles and 6 parts of nanocomposite materials to 200 parts of modified waterborne epoxy resin emulsion by mass, stirring at a speed of 700 r / min for 3 h to obtain a suspension with a concentration of 0.6 mg / mL;
[0103] S52, maintaining the stirring speed, adding 75 parts of PP, 6 parts of m-phenylenediamine, 5 parts of vinyltrimethoxysilane and 3 parts of antioxidant 1010 to the suspension, uniformly mixing for 3 hours, and drying in a drying oven at 190° C. for 7 minutes to obtain a mixture;
[0104] S53. The mixed material is passed through a twin-screw extruder granulator, and then melt blended, extruded, and pelletized to prepare the mildew-proof, flame-retardant, and formaldehyde-removing masterbatch. The temperature settings of the twin-screw extruder granulator are as follows: 210°C for the feeding section, 240°C for the compression section, 265°C for the homogenization section, 20r / min for the feeding speed, 350r / min for the screw speed, and 12m / min for the pelletizing speed.
[0105] Comparative Example 1
[0106] The difference between Comparative Example 1 and Example 1 is that hydroxyethyl cellulose is not added when preparing the modified waterborne epoxy resin emulsion in Comparative Example 1, and the other operations are the same.
[0107] Comparative Example 2
[0108] The difference between Comparative Example 2 and Example 1 is that the waterborne epoxy resin is not modified in Comparative Example 2, and the other operations are the same.
[0109] Comparative Example 3
[0110] The difference between Comparative Example 3 and Example 1 is that no aqueous acrylic emulsion is added in Comparative Example 3, and the other operations are the same.
[0111] Comparative Example 4
[0112] The difference between Comparative Example 4 and Example 1 is that nano titanium dioxide is not added in Comparative Example 4, and the other operations are the same.
[0113] Comparative Example 5
[0114] The difference between Comparative Example 5 and Example 1 is that in Comparative Example 5, the zeolite is not subjected to acid treatment, and the other operations are the same.
[0115] Comparative Example 6
[0116] The difference between Comparative Example 6 and Example 1 is that no zeolite is added in Comparative Example 6, and the other operations are the same.
[0117] Comparative Example 7
[0118] The difference between Comparative Example 7 and Example 1 is that in Comparative Example 7, magnesium oxide is not deposited on the surface of zeolite, and the other operations are the same.
[0119] Comparative Example 8
[0120] The difference between Comparative Example 8 and Example 1 is that the surface of the zeolite on which magnesium oxide is deposited in Comparative Example 8 is not subjected to amination treatment, and the other operations are the same.
[0121] Comparative Example 9
[0122] The difference between Comparative Example 9 and Example 1 is that in Comparative Example 9, the nano-titanium dioxide is not modified, and the other operations are the same.
[0123] Performance Test:
[0124] 1. Formaldehyde removal test: According to the test standard QB / T 2761-2006, removal rate (%) = (blank test chamber concentration value - sample test chamber concentration value) / blank test chamber concentration value × 100%, the results are shown in Table 1:
[0125] Table 1
[0126]
[0127] 2. Mildew resistance test: According to Appendix C of GB 21551.2-2010, rating standard: Grade 0: no growth, i.e. no growth observed under a microscope (magnification 50 times), Grade 1: trace growth, i.e. growth visible to the naked eye, but the growth coverage area is less than 10%, Grade 2: growth coverage area is less than 30%, but not less than 10% (mild growth), Grade 3: growth coverage area is less than 60%, but not less than 30% (moderate growth), Grade 4: growth coverage area is greater than 60% to full coverage (severe growth);
[0128] Test strains:
[0129] Aspergillus niger AS 3.4463,
[0130] Penicilium funiculosum AS 3.3875,
[0131] Aspergillus terreus AS 3.3935,
[0132] Aureobasidium pullulans AS 3.3984,
[0133] Chaetomium globosum AS 3.4254,
[0134] Paecilomvces variotii AS3.4253, the results are shown in Table 2:
[0135] Table 2
[0136]
[0137] 3. Flame retardant test: The masterbatch in the embodiment and the comparative example was pressed into a sample of 125×13×1.6 mm on an injection molding machine and tested according to GB∕T 2408-2021. The obtained data are shown in Table 3:
[0138] Table 3
[0139]
[0140] According to the above test data, the mildew resistance, formaldehyde removal rate and flame retardancy of Examples 1-3 are better than those of the comparative examples, so the plastic masterbatch prepared by the present invention has excellent mildew resistance, flame retardancy and formaldehyde removal performance. Comparative Examples 3, 4 and Comparative Examples 5, 6 show that the formaldehyde removal and flame retardancy of the material can be improved by amination of nano titanium dioxide and acid treatment of zeolite in the present invention. Comparative Examples 4-7 show that the effect achieved by the nanocomposite material obtained by compounding amination of nano titanium dioxide, acid-treated zeolite and magnesium oxide is better than that achieved by using one alone.
[0141] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A mildew-proof, flame-retardant and formaldehyde-removing masterbatch, Features: The composition is composed of the following mass parts: 10-20 parts of nano silver particles, 3-6 parts of nano composite materials, 100-200 parts of modified waterborne epoxy resin emulsion, 3-6 parts of meta-xylylenediamine, 60-75 parts of plastic masterbatch base material, 2-5 parts of coupling agent and 1-3 parts of antioxidant; The modified waterborne epoxy resin emulsion is prepared by the following steps: S11. At 35-40°C, stir 2-4 parts of emulsifier and 10-20 parts of deionized water to make them completely dissolved, thereby obtaining an emulsifier solution; S12, take 5-10 parts of carboxyethyl cellulose, add 10-20 parts of deionized water, stir at a temperature of 100-110°C until completely dissolved to obtain a cellulose solution, and fully stir the fiber solution and the emulsifier solution in a mass ratio of 1:1; S13, heating to 120-125°C, adding 40-60 parts of waterborne epoxy resin, 5-10 parts of glycidyl methacrylate, and 1-2 parts of sodium dodecylbenzene sulfonate, stirring evenly, adding 1-3 parts of initiator benzoyl peroxide, stirring at a speed of 600-800 r / min, and keeping warm for 4-5 hours, then cooling to 45-55°C, adding N,N-dimethylethanolamine to adjust the pH of the solution to 7-8, keeping warm for 0.5-1 hour at 40-45°C, filtering, and then adding 10-20 parts of waterborne acrylate emulsion and mixing well to obtain a modified waterborne epoxy resin emulsion; The nanocomposite material is prepared by the following steps: S21, placing the zeolite in a nitric acid solution with a mass fraction of 13-20% for 2-3 hours, taking it out and drying it to obtain the acid-treated zeolite; S22, add 1-3 parts of acid-treated zeolite to 10-50 parts of 3-7 mol / L magnesium chloride aqueous solution, adjust the pH to 8-9, react for 0.5-1 hour, calcine at 320-380° C. for 5-8 hours under nitrogen protection, and deposit magnesium oxide on the surface of the zeolite by in-situ deposition method after cooling to room temperature; S23, fully dissolving 3-aminopropyltriethoxysilane with anhydrous ethanol to prepare a solution with a mass fraction of 40-50%, adding 15-25 parts of the solid obtained in step S22 to 20-35 parts of the solution, stirring at a speed of 500 r / min for 5-10 min, filtering after standing for 2-3 hours, washing with deionized water, and drying the filter residue in a vacuum drying oven at a temperature of 110-120° C. for 3-5 hours to obtain amination solid particles; S24, at 60°C, 40 parts of 0.32-0.35 mol / L nickel acetate tetrahydrate in anhydrous ethanol and 10 parts of 0.2 mol / L phytic acid ethanol solution were mixed, and then 20-25 parts of nano titanium dioxide were added, and the temperature was raised to 80-90°C and stirred for reaction for 2 hours, and modified nano titanium dioxide was prepared by centrifugation, ethanol washing, drying, and grinding; S25, grinding 15 to 20 parts of the aminated solid particles and 15 parts of the modified nano titanium dioxide in a ball mill at a rotation speed of 400 r / min for 4 to 6 hours to obtain the nano-composite material.
2. The mildew-proof, flame-retardant and formaldehyde-removing masterbatch according to claim 1, Features: The coupling agent is one of vinyl trimethoxy silane, vinyl triethoxy silane and vinyl tri (2-methoxyethoxy) silane.
3. The mildew-proof, flame-retardant and formaldehyde-removing masterbatch according to claim 1, Features: The antioxidant is antioxidant 1010 or antioxidant 168.
4. The mildew-proof, flame-retardant and formaldehyde-removing masterbatch according to claim 1, Features: In step S11, the emulsifier is one of OP-10, Tween-80 and Span-80.
5. A method for preparing the mildew-proof, flame-retardant and formaldehyde-removing masterbatch according to any one of claims 1 to 4, Features: The following steps are involved: S51, adding nano silver particles and nano composite materials to the modified waterborne epoxy resin emulsion according to the proportion, stirring at a speed of 600-700 r / min for 2-3 hours to obtain a suspension; S52, maintaining the stirring speed, adding the plastic masterbatch base material, m-xylylenediamine, coupling agent and antioxidant into the suspension, uniformly mixing for 2-3 hours and then drying to obtain a mixture; S53. The mixed material is passed through a twin-screw extruder granulator, and then melt blended, extruded, and pelletized to prepare the mildew-proof, flame-retardant, and formaldehyde-removing masterbatch. The temperature settings of the twin-screw extruder granulator are as follows: 160-210°C for the feeding section, 170-240°C for the compression section, 175-265°C for the homogenization section, 5-20r / min for the feeding speed, 200-350r / min for the screw speed, and 8-12m / min for the pelletizing speed.
6. The method for preparing the mildew-proof, flame-retardant and formaldehyde-removing masterbatch according to claim 5, Features: In step S51, the concentration of the suspension is 0.3-0.6 mg / mL.
7. The method for preparing the mildew-proof, flame-retardant and formaldehyde-removing masterbatch according to claim 5, Features: In step S51, the nano silver particles have a particle size of 40-60 μm.
8. The method for preparing the mildew-proof, flame-retardant and formaldehyde-removing masterbatch according to claim 5, Features: In step S52, the plastic masterbatch substrate is one of polypropylene, polyethylene terephthalate, acrylonitrile-butadiene-styrene plastic and thermoplastic polyurethane elastomer.
9. The method for preparing the mildew-proof, flame-retardant and formaldehyde-removing masterbatch according to claim 5, Features: In step S52, the drying method is to place the mixture in a drying oven at 150-190°C for 5-7 minutes.
Citation Information
Cited By
Light heat-conducting engineering plastic master batch and preparation method thereof
CN120842620A
